2021
DOI: 10.1021/acsomega.1c01591
|View full text |Cite
|
Sign up to set email alerts
|

Discerning the Metal Doping Effect on Surface Redox and Acidic Properties in a MoVTeNbOx for Propa(e)ne Oxidation

Abstract: Adding a small quantity of K or Bi to a MoVTeNbO x via impregnation with inorganic solutions modifies its surface acid and redox properties and its catalytic performance in propa(e)ne partial oxidation to acrylic acid (AA) without detriment to its pristine crystalline structure. Bi-doping encourages propane oxydehydrogenation to propene, thus enlarging the net production rate of AA up to 35% more. The easier propane activation/higher AA production over the Bi-doped catalyst is ascrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Recently, a doping study on MoVTeNbO x with Bi showed a similar effect of increased AA selectivity, which was correlated to a more oxidized surface state and also an increased Lewis acidity. 104 In contrast, the MnO x -modified sample shows an even more reduced oxidation state of V compared to the base catalyst, which is maintained after reaction. Thus, the low AA selectivity measured on this catalyst is consistent with the discussion above.…”
Section: The Influence Of the Surface Modification On Catalysismentioning
confidence: 97%
“…Recently, a doping study on MoVTeNbO x with Bi showed a similar effect of increased AA selectivity, which was correlated to a more oxidized surface state and also an increased Lewis acidity. 104 In contrast, the MnO x -modified sample shows an even more reduced oxidation state of V compared to the base catalyst, which is maintained after reaction. Thus, the low AA selectivity measured on this catalyst is consistent with the discussion above.…”
Section: The Influence Of the Surface Modification On Catalysismentioning
confidence: 97%
“…48%, despite the decrease in the quantity of phase M1. 274 In a recent publication by our group, 259 the impregnation of MoVTeNbOx with inorganic solutions of K or Bi led to changes in the acid and RedOx surface properties that improved the catalytic behavior in propane oxidation to acrylic acid reaching yields of ca. 45% at 380 °C, with Bidoping participating earlier in propane's pathway compared to K-doping.…”
Section: Oxidative Dehydrogenation Of Propane Tomentioning
confidence: 99%
“…The main pathway to acrylic acid is accompanied by a set of side reactions yielding not only other oxygenate species (acetone, acetic acid, propanol, propanoic acid, etc.) but also the total oxidation product (Figure ); all these reactions are exothermic reactions, which is an important additional challenge in the catalyst design and the reactor configuration . The diverse formulations historically designed for catalyzing the direct oxidation of propane to acrylic acid have been classified into three general groups, namely, vanadium pyrophosphates (e.g., V–P–O, Fe–P–O, Mn–P–O, Cu–P–O, etc.…”
Section: Propanementioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that breaking the C-H bond is the limiting step in the oxidative dehydrogenation of propane and that this step occurs at the active site consisting of V ions on the surface of the M1 phase. Therefore, V 5+ ions are considered the active site for alkane activation [48,49]. In Fig.…”
Section: Structural Characterization Of Catalystsmentioning
confidence: 99%